PARP1 roles in DNA repair and DNA replication: The basi(c)s of PARP inhibitor efficacy and resistance - Kanev, Petar-Bogomil; Atemin, Aleksandar; Stoynov, Stoyno; Aleksandrov, Radoslav (Seminars in oncology, 2024)
Genome integrity is under constant insult from endogenous and exogenous sources. In order to cope, eukaryotic cells have evolved an elaborate network of DNA repair that can deal with diverse lesion types and exhibits considerable functional redundancy. PARP1 is a major sensor of DNA breaks with established and putative roles in a number of pathways within the DNA repair network, including repair of single- and double-strand breaks as well as protection of the DNA replication fork. Importantly, PARP1 is the major target of small-molecule PARP inhibitors (PARPi), which are employed in the treatment of homologous recombination (HR)-deficient tumors, as the latter are particularly susceptible to the accumulation of DNA damage due to an inability to efficiently repair highly toxic double-strand DNA breaks. The clinical success of PARPi has fostered extensive research into PARP biology, which has shed light on the involvement of PARP1 in various genomic transactions. A major goal within the field has been to understand the relationship between catalytic inhibition and PARP1 trapping. The specific consequences of inhibition and trapping on genomic stability as a basis for the cytotoxicity of PARP inhibitors remain a matter of debate. Finally, PARP inhibition is increasingly recognized for its capacity to elicit/modulate anti-tumor immunity. The clinical potential of PARP inhibition is, however, hindered by the development of resistance. Hence, extensive efforts are invested in identifying factors that promote resistance or sensitize cells to PARPi. The current review provides a summary of advances in our understanding of PARP1 biology, the mechanistic nature, and molecular consequences of PARP inhibition, as well as the mechanisms that give rise to PARPi resistance.